2018
DOI: 10.15388/na.2018.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-time control of delayed neural networks with impulsive perturbations

Abstract: This paper is concerned with the fixed-time stability of delayed neural networks with impulsive perturbations. By means of inequality analysis technique and Lyapunov function method, some novel fixed-time stability criteria for the addressed neural networks are derived in terms of linear matrix inequalities (LMIs). The settling time can be estimated without depending on any initial conditions but only on the designed controllers. In addition, two different controllers are designed for the impulsive delayed neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…Set V(t) = V(t, x(t)) and (t) = (t − t 0 ), where scalar > 0 and we can observe that (t) ∈ K 0 . By Corollary 2, we obtain that condition (7) can be reduced by Moreover, if there is a satisfying (25), and then we have…”
Section: Corollary 2 Under the Conditions In Theorem 1 The Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…Set V(t) = V(t, x(t)) and (t) = (t − t 0 ), where scalar > 0 and we can observe that (t) ∈ K 0 . By Corollary 2, we obtain that condition (7) can be reduced by Moreover, if there is a satisfying (25), and then we have…”
Section: Corollary 2 Under the Conditions In Theorem 1 The Systemmentioning
confidence: 95%
“…We can find earlier works on impulsive systems in the works of Lakshmikantham et al and Benchohra et al The impulsive system is generally regarded as an important type of hybrid system. Specifically, the impulsive system is composed of three parts, ie, continuous evolution, discrete evolution, and an impulsive rule, determining when the impulses happen . The stability analyses of impulsive systems have been extensively investigated by many investigators .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recent studies and experiments on neural network models indicated that impulsive control is more effective in their numerous applications mainly because it allows the control actions only at some discrete instances. That is why different classes of impulsive control neural networks, including CNNs, have been massively studied in the literature [49][50][51][52].…”
Section: Applications and Examplesmentioning
confidence: 99%
“…Motivated by some ideas and methods in [16,[32][33][34][35][36][37][38][39][40]46], we are to investigate the stability of a class of p-Laplacian diffusion T-S fuzzy system via variational methods that are different from those of existing literature related to reaction-diffusion fuzzy systems.…”
Section: Introductionmentioning
confidence: 99%